Socio-environmental REDD+ safeguards in Brazil: analyzing the Amazon Fund - Aparicio, Jorge Ernesto Salvador Bazán; Paulino , Sonia (Technical and Scientific Journal Green Cities, 2025)
Objective – Discuss REDD+ safeguards in the Amazon Fund (AF), from 2008 to 2025.Methodology – Narrative literature review and documentary analysis. Four aspects were considered for safeguards analysis: objectives, beneficiaries, operationalization, and results.Originality/Relevance – The topic is little explored in the scientific literature. This article explores socio-environmental aspects of a globally relevant climate fund for climate change mitigation, allowing for important conclusions to be drawn for public policy that considers the challenges raised in the study and climate justice.Results – The positive aspects of the evolution of safeguards in the FA include: pioneering in the adoption of safeguards, the adoption of knowledge generated by civil society, the alignment with REDD+ and methodological advances such as conceptual frameworks for evaluation and guidelines. On the other hand, the following challenges were observed: limitations in transparency and disclosure, lack of clarity regarding sources and current mechanisms for safeguards, and vulnerability to the political context. Considering objectives, beneficiaries, operationalization, and results related to safeguards, the positive aspects include the expansion of priorities and a heterogeneous approach to projects beyond carbon results, the generation of co-benefits, and a broad scope of beneficiaries. Critical observations include the FA being viewed more as a "mechanism for economic innovation" than a "mechanism for social transformation," its effectiveness and ability to demonstrate social impacts are limited, and that there is a lack of incentives for local and multi-level action.Theoretical/Methodological Contributions – The analysis allowed us to systematize the main documents of the Amazon Fund on safeguards and raise the main debates in the scientific literature.Social and Environmental Contributions – Safeguards inherently address social and environmental issues, and we observed that in the Amazon Fund they relate to climate justice and social and environmental benefits beyond carbon results.
Keywords: Socio-environmental safeguards; Climate finance; Deforestation